Policy Scenario to Boost East Java Economic Recovery: Interregional Input-Output Analysis (IRIO) - Doddy Purwoharyono; Fathia Khairunnisa; Achmad Rifa'i (Journal of Asset Management and Public Economy (JAMPE), 2023)
Economic recovery post-COVID-19 is the major development agenda of the government at the central and regional levels. The contribution of this study is to identify, analyze, and provide strategic policy recommendations on the progress of economic recovery in East Java using Input-Output (IO) model. As one of the provinces with the 2nd highest economic contribution to the nation, East Java needs to develop a comprehensive economic recovery strategy to lift its economy to a higher position than the pre-pandemic level. First, the recommended policy scenario is based on the results of the calculation of the recovery index for the Province and Regency/City of East Java. Hereafter, using the 2016 Interregional Input-Output (IRIO) Table, this study recommends a stimulus policy scenario for investment and government spending in all sectors as a game changer that will accelerate East Java's economic recovery. Meanwhile, by sector, information and communication will be the main sectors that encourage the acceleration of economic recovery in East Java Province. Nevertheless, the stimulus in each policy scenario can be considered by the East Java Provincial Government according to the focus and objectives of economic recovery.